Bridgett A. Green named president and publisher of Presbyterian Publishing Corporation. (Christian Century, 2026)
The article announces Bridgett A. Green's appointment as president and publisher of Presbyterian Publishing Corporation, marking a historic moment as she becomes the first woman and first Black American to lead the denomination's official publishing arm.